2010
DOI: 10.1136/tc.2010.037259
|View full text |Cite
|
Sign up to set email alerts
|

Electronic nicotine delivery systems: is there a need for regulation?

Abstract: Design flaws, lack of adequate labelling and concerns about quality control and health issues indicate that regulators should consider removing ENDS from the market until their safety can be adequately evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
128
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 12 publications
2
128
0
2
Order By: Relevance
“…EC have a mouthpiece containing a fluid-filled cartridge, an atomizer used to vaporize the cartridge fluid, and a battery that powers the atomizer [3]. The cartridge fluid usually contains nicotine, flavorings, and a humectant that when heated by the atomizer creates an inhalable aerosol.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…EC have a mouthpiece containing a fluid-filled cartridge, an atomizer used to vaporize the cartridge fluid, and a battery that powers the atomizer [3]. The cartridge fluid usually contains nicotine, flavorings, and a humectant that when heated by the atomizer creates an inhalable aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic cigarettes (EC) are nicotine delivery devices that are rapidly gaining acceptance as an alternative to conventional cigarettes with little knowledge regarding their effects on prenatal development or adult health [1][2][3]. EC have a mouthpiece containing a fluid-filled cartridge, an atomizer used to vaporize the cartridge fluid, and a battery that powers the atomizer [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the quality control test for the device has not been adequately performed. It was found that users can modify it for using addictive substances such as hashish (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…This aerosolizing delivery device is compatible with a disposable cartridge, which contains nicotine in solution of propylene glycol as the humectant. The devices are composed of a battery, a heating element, a power source, and a pressure switch (Trtchounian & Talbot, 2011). All these components are embedded in a tube with a mouthpiece (Figure 2.3), and the construction of device may vary.…”
Section: Electronic Nicotine Delivery Device (E-cigarette)mentioning
confidence: 99%